O desempenho do mercado (Focus) na previs\~ao da inflaç\~ao: Novos resultados? - Elcyon Caiado Rocha Lima; Paloma Palmieri Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The evaluation of forecasts performance of market expectations about the Brazilian inflation rate (Focus survey) is important given the prominent role of these expectations in the conduction of monetary policy in Brazil. Lima e Céspedes (2006) showed that, in the period 2000.1 2005.4, several models had superior forecast ability than the mean of market inflation rate (measured by IPCA) forecasts for horizons superior to three months. In this article, using more recent information, we found no significant evidence that the mean of market forecasts had superior forecast ability than some univariate autoregressive models.
Keywords: E31; E52; C53; 330; Inflation; Prognoseverfahren; Brasilien